The Aquitaine Shelf Edge (Bay of Biscay): A Primary Outlet for Microbial Methane Release. Issue 7 (4th April 2020) - Dupré, S.; Loubrieu, B.; Pierre, C.; Scalabrin, C.; Guérin, C.; Ehrhold, A.; Ogor, A.; Gautier, E.; Ruffine, L.; Biville, R.; Saout, J.; Breton, C.; et al.
Abstract: A few thousand (2, 612) seeps are releasing microbial methane bubbles from the seafloor at the Aquitaine Shelf edge (Bay of Biscay) at shallow water depths (140–220 m). This methane contributes to the formation of meter‐scale subcircular carbonate structures, which are (sub)outcropping over 375 km 2 . Based on in situ flow rate measurements and acoustic data, and assuming steady and continuous fluxes over time, the methane entering the water column is estimated at 144 Mg/yr. Microbial methane circulation has been ongoing for at least a few thousand years. This discovery highlights the importance of microbial methane generation, disconnected from deep thermogenic sources and gas hydrates, at continental shelves. The shelf edge may be viewed as a focus area for methane circulation and release and related diagenesis, all having an impact on the shaping of continental shelves and potentially on the oceanic and atmospheric carbon budget. Plain Language Summary: At the Aquitaine Shelf of the Bay of Biscay (Northeast Atlantic Ocean), the recent acoustic, chemical, and visual investigations of microbial methane release at the seafloor have led to the discovery of a vast fluid system. This methane escapes as bubbles from the seafloor into the seawater at 2, 612 sites, all located at shallow water depths (140–220 m) along the edge of the continental shelf. Methane‐derived authigenic carbonates that are by‐products of gas seepage cover the (sub)seafloor over a large area of 375 km 2 . These carbonates form subcircular meter‐scale pavements and mounds, less than 2 m in height above the surrounding seafloor. Based on the growth rate of authigenic carbonates, it can be inferred that methane circulation has occurred for at least a few thousand years. The amount of methane released from the Aquitaine Shelf seafloor into the water column, estimated at 144 t/yr, questions the fate of the methane in the ocean and its possible passage to the atmosphere with therefore consequent potential contribution to the oceanic and atmospheric carbon budget over time. Key Points: Up to 2, 612 gas bubbling sites at the Aquitaine Shelf edge release 144 Mg/yr of microbial methane into the water column Methane‐derived authigenic (sub)outcropping carbonates cover 375 km 2 Methane‐rich fluids have been circulating for at least a few thousand years